History of public food interventions in Bangladesh - Haggblade, Steven (International Food Policy Research Institute, 2000)
Since the 1940s, the Ministry of Food and its predecessor agencies have been the single largest purchaser, importer, stockholder, and distributor of foodgrains in Bangladesh. During World War II the government in British India laid the foundation for large-scale public marketing by arrogating large powers for itself: monopolies on foodgrain imports and tight control of procurement, movement, stockholding, and distribution. At the same time it adopted legislation severely restricting foodgrain movement and stockholding by private traders. This chapter outlines the evolving administrative structure, scope, and objectives of this direct buying and selling by public agents.